Scandia stabilized zirconia-ceria solid electrolyte (xSc1CeSZ, 5 < x < 11) for IT-SOFCs: Structure and conductivity studies. (August 2016) - Kumar, Ashutosh; Jaiswal, Abhishek; Sanbui, Mohit; Omar, Shobit
Abstract: The current study looks at Sc2 O3 (5–11 mol%) stabilized ZrO2 -CeO2 solid electrolyte for application in IT-SOFCs. Using XRD, Raman spectroscopy, and impedance spectroscopy, it was found that the addition of 1 mol% CeO2 in the ZrO2 host-lattice increases the tendency to form high-symmetry, high-conductivity phases at the expense of low-symmetry, low-conductivity phases, resulting in higher total ionic conductivity. Moreover, the conductivity maximum has broadened and shifted to lower Sc2 O3 content. The phase equilibria and conductivity results are explained on the basis of larger ionic size of Ce 4 +, which enforces higher symmetry as evidenced by lower axial ratio ( c / a ) in tetragonal phase. Graphical abstract: